Pathologic Roles of Receptor-Associated Prorenin System in Idiopathic Epiretinal Membrane - Dong, Yoko (Sci Rep, 2017)
Receptor-associated prorenin system (RAPS) refers to the pathogenic mechanism whereby prorenin binding to (pro)renin receptor [(P)RR] dually activates tissue renin-angiotensin system (RAS) and RAS-independent signaling via (P)RR. The aim of this study is to determine the association of RAPS with idiopathic epiretinal membrane (iERM). Reverse transcription-PCR indicated the expression of RAPS components, including (P)RR and Ang II type 1 receptor (AT1R), in iERM tissues and human Müller glial cell line. Double-labeling analyses demonstrated that (P)RR and AT1R were detected in cells positive for glial fibrillary acidic protein, a marker for glial cells, and co-localized with prorenin and angiotensinogen, respectively. Administration of prorenin to Müller glial cells enhanced mRNA expression of fibroblast growth factor 2, while Ang II application stimulated the expression of glial cell line-derived neurotrophic factor, nerve growth factor, and transforming growth factor-β1. These expression levels induced by prorenin or Ang II were reversed by (P)RR or AT1R blockade, respectively. Immunofluorescence revealed tissue co-localization of (P)RR and AT1R with the products of the upregulated genes in vitro. The present findings suggest the involvement of RAPS in the pathogenesis of iERM.